Topical delivery of coenzyme Q10-loaded microemulsion for skin regeneration - Ryu, Kyeong A.; Park, Phil June; Kim, Seong Bo; Bin, Bum Ho; Jang, Dong Jin; Kim, Sung Tae (Pharmaceutics, 2020)
The aim of this study was to develop a coenzyme Q10 (CoQ10) microemulsion system with improved solubility, penetration, and wound healing efficacy. Based on the pseudo-ternary diagram, microemulsions containing isopropyl myristate (IPM), Cremophor EL®, and Transcutol® HP were selected and confirmed to be nanosized (<20 nm) and thermodynamically stable based on the dilution and thermodynamic stability tests. The CoQ10-loaded microemulsion with a surfactant/co-surfactant (S/CoS) ratio of 2:1 (w/w %) demonstrated a higher permeation efficacy compared to microemulsions with S/CoS ratio of 3:1 or 4:1 (w/w %). Additionally, the CoQ10-loaded microemulsion with an S/CoS ratio of 2:1 demonstrated a relatively rapid wound healing effect in keratinocytes and fibroblasts. Overall, these data suggest that a microemulsion based on IPM, Cremophor EL®, and Transcutol® HP could be an effective vehicle for the topical administration of CoQ10 and could be utilized for the application of other therapeutic agents that have difficulty in penetrating the skin.
Keywords: Coenzyme Q10; Microemulsion; Skin regeneration; Topical administration